(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The primary objective of this project is to provide a clear picture by connecting the dots between the numerous energy options available to humans. For humans to thrive in today’s highly developed society, travel is a need. And to do that, he needs to make as few trips as possible. The electric bike described here is powered by a battery that sends electricity to the bike’s engine. An Electric Bike, powered primarily by electricity, is the focus of this project’s design and construction efforts. Since the bike is powered by electricity rather than gasoline, it can achieve better fuel economy, higher performance, and lower pollution levels than conventional vehicles. In an effort to lessen both noise and air pollution. It gives a more fuel-efficient and environmentally friendly car. As a result, the transmission is also utilised to regulate the acceleration and deceleration of the vehicle. Electricity, not gasoline, diesel, or any other fuel, has sparked a revolution in India’s motorcycle market. The two-wheeler business in India has jumped on the bandwagon of the increasingly popular electric bike and scooter in the West and East. Therefore, the future of personal transportation is electric bikes and scooters. This research venture examines the design and development process and evaluates the performance of several subsystems. The project also details the functions of the various electric two-wheeler parts, including the battery, charger, hub motor, and controller.